2020
DOI: 10.3390/nu12082209
|View full text |Cite
|
Sign up to set email alerts
|

Third-Trimester Glucose Homeostasis in Healthy Women Is Differentially Associated with Human Milk Oligosaccharide Composition at 2 Months Postpartum by Secretor Phenotype

Abstract: Human milk oligosaccharides (HMOs) are bioactive molecules in human milk that play a critical role in infant health. Obesity and associated metabolic aberrations can negatively impact lactation and alter milk composition. Here, the relationship between maternal glucose homeostasis and HMO composition from 136 healthy women was examined. Maternal glucose homeostasis (fasting plasma glucose and insulin, homeostatic model assessment for insulin resistance, and insulin sensitivity index) was evaluated at 30 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 45 publications
(68 reference statements)
2
18
1
Order By: Relevance
“…Approximately 73% of the total population was phenotypically determined to be secretors, based on a human milk 2’FL concentration of >100 nmol/mL at 2 months postpartum. A greater proportion of women with OW (31.4%) or OB (33.3%) were phenotyped as non-secretors compared to women with NW (16.2%), consistent with our previous findings [ 17 ]. The overall cohort consisted mostly of Caucasian women (81.4%) who were approximately 30 years of age.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Approximately 73% of the total population was phenotypically determined to be secretors, based on a human milk 2’FL concentration of >100 nmol/mL at 2 months postpartum. A greater proportion of women with OW (31.4%) or OB (33.3%) were phenotyped as non-secretors compared to women with NW (16.2%), consistent with our previous findings [ 17 ]. The overall cohort consisted mostly of Caucasian women (81.4%) who were approximately 30 years of age.…”
Section: Resultssupporting
confidence: 92%
“…Maternal genetics (expression patterns of Secretor (Se) and Lewis (Le) gene alleles, which code for different fucosyltransferases) have the greatest impact on HMO composition [ 26 ]. However, we and several others have concluded that various maternal characteristics (age, race, ethnicity, and parity) including pre-pregnancy BMI [ 10 , 11 , 17 ] and maternal glucose homeostasis [ 17 ] can affect HMO composition during lactation. To our knowledge, this study presented herein is one of the first to explore the relationship between maternal BMI and HMO composition in a large group of women whose BMIs encompassed Class I–Class III obesity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This lack of HMOs may induce consequences for metabolic activities, especially diarrheal diseases, in infants (23). On the other hand, women without functional FUT3 cannot produce HMOs with a1,3/4 fucosyl linkages such as 3'-FL and LNFPII (24). Recently, glucose levels in the blood of the mother were shown to affect the composition of HMOs in breastmilk.…”
Section: Structure Of Hmos and Their Compartmentalization In Mothers And Childrenmentioning
confidence: 99%